Two-phase fin-induced turbulent cooling for electronic devices using heat pump associated micro-gap Heat Sink - Ahmed, Shugata; Sulaeman, Erwin; Ismail, Ahmad Faris; Muhammad, Hasibul Hasan (Science Publishing Corporation, 2018)
High energy requirement for electronic cooling is a major problem to operate high performance computers and data centres. Developing low cost thermal management systems for micro-electronic devices and micro-electro-mechanical systems (MEMS) is a cutting edge research area. A heat pump system associating micro-gap evaporator with internal micro-fins is a potential candidate for two-phase cooling of these advanced devices. Micro-fins induce pseudo-turbulence in the flow field, which escalates heat transfer rate. In this paper, the system per-formance of a heat pump using micro-gap evaporator has been investigated numerically and experimentally. As heat transfer rate in the mi-cro-gap evaporator is influenced by turbulence generation, flow field in the inlet and outlet manifolds have been visualized in the numerical simulation to observe fin-induced pseudo-turbulence at the entrance and outlet of the micro-gap evaporator. The simulation has been per-formed using FLUENT 14.5 release. Experimental work has been carried out to validate numerical results. For experimentation purpose, a test rig has been developed, which contains a test section accommodating the micro-gap evaporator. A heater is provided at the bottom of the evaporator to supply uniform heat flux ranging 1 ~ 8 kW/m2. A pre-heater is installed at the compressor outlet to vary refrigerant tempera-ture at the condenser inlet. The range of pre-heater temperature is 93 ~ 159°C. A variable speed compressor is used. The input frequency to the compressor is varied within the range of 20 ~ 50 Hz to run the compressor at different speeds. Experimental data show good agreement with numerical results. It is observed that in transient state, temperatures and pressures at different locations of the test apparatus fluctuate due to quasi-periodic dry out and surface rewetting nature of the flow. When pre-heater temperature is set at 159⁰C and compressor fre-quency is increased from 20 Hz to 30 Hz, evaporator wall heat flux escalates 118.2% and heat transfer rate of the condenser increases 65.2%. However, heat transfer rate declines with the further increment of compressor frequency. Coefficient of performance (COP) of the heat pump also increases with the frequency increment from 20 Hz to 30 Hz and declines after surpassing 40 Hz frequency.